Site Selection of Appropriate Locations for Development of Orchards Using GIS & RS, by Emphasizing Climatic Factors (Case study: Walnut - Tehran Province) - Fatemeh Falahati; Bahlool Alijani; Manizha Ghohrodi Tali; Mohammadjavad Barati (جغرافیا و پایداری محیط)
Climatic factors are the most important variables among effective factors in agricultural production, which cost us too much to control. The main objective of this study is to investigate climatic factors in determining suitable locations for new orchards (case study Walnut). According to Walnut compatibility patterns, non-suitable areas were removed and suitable areas were selected. This method is called step by step elimination and the advantages of this method are reducing the cost and time. In this study incompatibility of each parameter results in the destruction of the plant and barrenness of the region, so at first step, According to F.A.O classification elevation and slope were determined, as the two main factors, and digital data of them were analyzed, hereby non-potential areas were removed. Then, all the other effective factors like climate, chilling requirements, wind speed, and relative humidity were studied in the suitable and selected areas. Finally, according to land use map, suitable locations were suggested, and furthermore precipitation factor was evaluated in suitable location to determine irrigation needs too. The result showed that, the area about 630094.2 hectares of Tehran province can be planted by Walnut, which is shown in the final map. Due to high economic value of this product in agricultural export, it is recommended that Walnut orchards development should be considered in 4th program. Keywords